Forage Sorghum and Corn Silage Response to Full and Deficit Irrigation - I. Kisekka; J. D. Holman; J. W. Waggoner; J. Aguilar; R. Currie (Kansas Agricultural Experiment Station Research Reports, 2016)
There is limited information on forage sorghum and corn silage yield response to full and deficit irrigation in Kansas. The objective of this study was to generate information on forage sorghum (brown mid-rib hybrids (BMR and non-BMR)) and corn silage yield response to different levels of irrigation as influenced by irrigation capacity in southwest Kansas. Preliminary results indicate the effect of irrigation capacity on forage yield was significant (P = 0.0009) in 2014 but not 2015, probably due to high growing season rainfall received in 2015. Corn silage produced significantly (p<0.05) higher biomass at all irrigation capacities compared to forage sorghum hybrids in 2015. BMR forage sorghum produced significantly lower biomass compared to non-BMR hybrid in both 2014 and 2015 (P<0.05). The highest amounts of forage produced for corn silage, BMR, and non-BMR forage sorghum were 24.6, 17.4, and 21.1 tons/a adjusted to 65%, moisture respectively. Water productivity ranged from 1.0 to 1.4 dry matter tons/a/in. More research is needed under normal and dry years to quantify forage sorghum and corn silage yield and forage quality response to full and deficit irrigation.
Keywords: forage sorghum; corn silage; full and deficit irrigation; irrigation management; crop water use; non-BMR forage sorghum; BMR forage sorghum